2013
DOI: 10.1556/achrom.25.2013.3.5
|View full text |Cite
|
Sign up to set email alerts
|

Determination of fluoxetine in the presence of photodegradation products appearing during UVA irradiation in a solid phase by chromatographic-densitometric method, kinetics and identification of photoproducts

Abstract: Summary. An effect of ultraviolet A (UVA) radiation on fluoxetine stability in solid phase with and without the presence of selected metal ions was studied using the chromatographic-densitometric method. Silica gel TLC F 254 plates were used as the stationary phase and chloroform-methanol-ammonia 25% ( The liquid chromatography-electrospray ionization/mass spectrometry (LC-ESI/MS) method was applied for the identification of decomposition products noting the presence of 3-phenyl-3-hydroxypropylamine and 4-trif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 37 publications
(37 reference statements)
0
2
0
Order By: Relevance
“… Fluoxetine SS; MetOH; Water; HCl; NaOH N/A HPLC None 2 detected (Pathak and Rajput 2009 ) Solid state UV-C HPTLC None None (photostable) (Shah et al 2008 ) Water; SFW 290–800 nm Spectroph. HPLC IC HPLC–MS/MS None 4 identified (Lam et al 2005 ) SS UV-A HPLC–MS None 2 identified (Maalanka et al 2013 ) Water + Ga 2 O 3 UV-C IC UV–VIS Ames Test 2 photoproducts (defluorination and oxidation) (Hidaka et al 2013 ) Water + TiO 2 UV–VIS Spectroph. None None (da Silva et al 2015 ) Water; O 3 ; TiO 2 ; H 2 O 2 Hg lamp (360 nm) HPLC–MS None 4 identified (Méndez-Arriaga et al 2011 ) Fluvoxamine Water + Ga 2 O 3 UV-C IC UV–VIS None 1 (product of defluorination) (Hidaka et al 2013 ) Aqueous buffers; SHW UV sunlight simulation Spectroph.…”
Section: Photodegradation Studies On Psychotropic Drugsmentioning
confidence: 99%
“… Fluoxetine SS; MetOH; Water; HCl; NaOH N/A HPLC None 2 detected (Pathak and Rajput 2009 ) Solid state UV-C HPTLC None None (photostable) (Shah et al 2008 ) Water; SFW 290–800 nm Spectroph. HPLC IC HPLC–MS/MS None 4 identified (Lam et al 2005 ) SS UV-A HPLC–MS None 2 identified (Maalanka et al 2013 ) Water + Ga 2 O 3 UV-C IC UV–VIS Ames Test 2 photoproducts (defluorination and oxidation) (Hidaka et al 2013 ) Water + TiO 2 UV–VIS Spectroph. None None (da Silva et al 2015 ) Water; O 3 ; TiO 2 ; H 2 O 2 Hg lamp (360 nm) HPLC–MS None 4 identified (Méndez-Arriaga et al 2011 ) Fluvoxamine Water + Ga 2 O 3 UV-C IC UV–VIS None 1 (product of defluorination) (Hidaka et al 2013 ) Aqueous buffers; SHW UV sunlight simulation Spectroph.…”
Section: Photodegradation Studies On Psychotropic Drugsmentioning
confidence: 99%
“…The analytical methods used to estimate Fluoxetine are the subject of comprehensive research. As a single and multi-component, UV Spectrophotometry [6][7][8], High Performance Liquid Chromatography [9][10][11][12][13][14], High Performance Thin Layer Chromatography [15][16][17][18][19][20][21], the approach is inefficient since this described HPTLC technique only uses one variable at a time. It produces misleading findings that should be avoided.…”
Section: İd İd İdmentioning
confidence: 99%